National policy brokering and the construction of the European Education Space in England, Sweden, Finland and Scotland - Grek, S; Lawn, M; Lingard, B; Ozga, J; Rinne, R; Segerholm, C; Simola, H (2009)
This paper draws on a comparative study of the growth of data and the changing governance of education in Europe. It looks at data and the 'making' of a European Education Policy Space, with a focus on 'policy brokers' in translating and mediating demands for data from the European Commission. It considers the ways in which such brokers use data production pressures from the Commission to justify policy directions in their national systems. The systems under consideration are Finland, Sweden, and England and Scotland. The paper focuses on the rise of Quality Assurance and Evaluation mechanisms and processes as providing the overarching rationale for data demands, both for accountability and performance improvement purposes. The theoretical resources that are drawn on to enable interpretation of the data are those that suggest a move from governing to governance and the use of comparison as a form of governance.